New instruments for banking regulation and monetary policy after the crisis - Daniel Detzer (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2012)
This paper analyzes two instruments - asset-based reserve requirements put forward by Thomas Palley and asset-based capital requirements proposed by Charles Goodhart and Avinash Persaud - regarding their merits in reducing excessive asset price inflation. A theoretical framework of asset pricing based on the ideas of Keynes and Minsky is developed, within which the working of the instruments is demonstrated and analyzed. It is shown that in theory both instruments are able to reduce excessive asset price inflation by reducing the amount of credit money and investment flowing from financial institutions into a booming sector. It is found that asset-based reserve requirements will only work through a predictable price effect, while the effect of asset-based capital requirements is hard to predict and may even become a quantitative supply constraint. Hence, it is concluded that due to the higher predictability of asset-based reserve requirements those are more suitable for the task of tackling asset price bubbles.
Keywords: E00; E12; E52; G12; G18; 330; Monetary Policy; Banking Regulation; Asset Prices; Bubbles; Minsky; Financial Instability Hypothesis; Asset Based Reserve Requirements; Capital Requirements; Macroprudential Regulation